Department of Urdu, University of Peshawar - Khan, Samiullah; Shah, Mutahir; Rahman, Muhaammad (sourcecoder, 2022)
Sence related experiences are exiabated the bourn of imagery that’s why poetry constructed on Images, moved that the readers. The poetry of Saqi Farooqui is highly loaded with examples of Imagery’s his poetry contain diffwrent sensual Images. Particularly viusul imagert is more dynamic in it. Generally his poetry reveals mixed Imagery and hiz use of Imagery seems more unique and appealing. Usually in poem Imagery find genrus room but in Saqi Faroqui odes larish use of Imagery can be seen. However in his poems the use imagery is more detailed and white in his odes.